Analyzing the Optical Properties of Carom Water at Different Temperature and Concentration - Hangsarumba, Surendra; Das, Santosh Kumar; Hussain, Saddam (Patan Prospective Journal, 2024)
Carom water, infused with the seeds of Ajwain (Carom seeds), has been traditionally used for its medicinal properties. Its optical characteristics, such as transmittance and absorbance, can provide valuable insights into its composition and the effects of various external factors. This study investigates the optical properties of carom seed-infused water (carom water), focusing on the effects of soaking duration, sugar concentration, and temperature on transmittance and absorbance. After the preparation of sample of carom water, a Theremino spectrometer is used to measured transmittance and absorbance within the visible spectrum (380-700 nm) at various condition [various soaking periods, seed concentrations, and temperatures (30°C and 60°C)]. The study revealed that over time, transmittance decreases and absorbance increases as organic compounds from the seeds dissolve into the water, with higher seed concentrations accelerating this process. The addition of sugar altered the optical properties, with higher sugar concentrations leading to larger colloid formation and reduced transmittance. Temperature also influenced the optical characteristics, with higher temperatures promoting finer particles and increased transmittance. The findings suggest that soaking duration, sugar concentration, and temperature are key factors affecting the optical properties of carom water. Future research should focus on the molecular interactions between sugar and carom seed compounds and extend the spectral analysis to a broader wavelength range to gain deeper insights into these dynamic light-sample interactions.